Involvement of CYP1B1 in interferon γ‐induced alterations of epithelial barrier integrity. (4th February 2018) - Alhouayek, Mireille; Gouveia‐Figueira, Sandra; Hammarström, Marie‐Louise; Fowler, Christopher J
Abstract : Background and Purpose: CYP1B1 and CYP1A1 are important extra‐hepatic cytochromes, expressed in the colon and involved in the metabolism of dietary constituents and exogenous compounds. CYP1B1 expression is increased by pro‐inflammatory cytokines, and it has been recently implicated in regulation of blood brain barrier function. We investigated its involvement in the increased permeability of the intestinal epithelial barrier observed in inflammatory conditions. Experimental Approach: Epithelial monolayers formed by human T84 colon carcinoma cells cultured on transwells, were disrupted by incubation with IFNγ (10 ng·mL −1 ). Monolayer integrity was measured using transepithelial electrical resistance. CYP1A1 and CYP1B1 inhibitors or inducers were applied apically. Potential mechanisms of action were investigated using RT‐qPCR. Key Results: IFNγ disrupts the barrier integrity of the T84 monolayers and increases CYP1B1 and HIF1α mRNA expression. CYP1B1 induction is inhibited by the NF‐κB inhibitor ammonium pyrrolidinedithiocarbamate (100 μM) but not by the HIF1α inhibitor 3‐(5′‐hydroxymethyl‐2′‐furyl)‐1‐benzyl indazole (50 μM). Inhibition of CYP1B1 with the selective inhibitor 2, 4, 3′, 5′‐tetramethoxystilbene (100 nM) partly reverses the effects of IFNγ on epithelial permeability. Conclusions and Implications: These data suggest that increased expression of CYP1B1 is involved in the effects of IFNγ on epithelial permeability. Inhibition of CYP1B1 counteracts the alterations of epithelial barrier integrity induced by IFNγ and could thus have a therapeutic potential in disorders of intestinal permeability associated with inflammation.